Temperatures profiles of PV module at GERC: article / Hasan Basri Nordin - Nordin, Hasan Basri (2009)
Temperatures of PV module has known to be one of the parameter than varies the performance of photovoltaic. The output current and voltage of photovoltaic module are correlated with the module's temperature. This research is specialized to examine the temperatures profiles of PV module for open circuit and close circuit condition with and without air ventilations at the bottom of the PV modules at standalone structures. The thermocouples are placed at the back of the PV module at 8 different locations. Temperatures are taken for every 5 minutes for one week for each 4 difference condition at the same 8 thermocouples location. Besides that, the temperatures of metal deck PV modules structure are taken at close circuit condition and to be compared with stand-alone PV modules temperatures. The results recorded are analyzed based on the variables.